2012
DOI: 10.3109/02656736.2012.675116
|View full text |Cite
|
Sign up to set email alerts
|

Surgical options in early cervical cancer

Abstract: Cancer of the cervix is the second most common cancer in women worldwide and the fourth leading cause of cancer mortality in women. Early cervical cancer stage IB1 includes a broad range of disease from clinically undetectable microinvasive cancer to bulky tumours that infiltrated the entire cervix. This article reviews the literature about risk factors and surgical radicality and fertility-sparing surgery in early cervical cancer. The review evaluates selection criteria, preoperative management and the most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…This study showed an 8.4% (24/284) rate of LNM in patients with FIGO stage IB1 CC, a finding that is in accordance with those of other studies ( 12 14 ). The 5-year OS rate in patients with LNM was significant lower than patients without LNM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study showed an 8.4% (24/284) rate of LNM in patients with FIGO stage IB1 CC, a finding that is in accordance with those of other studies ( 12 14 ). The 5-year OS rate in patients with LNM was significant lower than patients without LNM.…”
Section: Discussionsupporting
confidence: 93%
“…However, some patients experience sequelae from this procedure (such as vascular or nerve injury, pelvic lymphocyst, and lower-limb lymphedema), which may increase the length of hospital stay and affect quality of life ( 7 9 ). In addition, the rate of LNM in FIGO stage IB1 patients was 7–17.4% ( 12 14 ). Lymphadenectomy may not have a survival benefit, but it may increase the incidence of postoperative complications in LNM-negative patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Best results are obtained by electrosurgical procedures using a needle (NETZ) or loop (LLETZ) with radiofrequency energy. In IA1 with LVSI tumours, a lymphadenectomy must be combined with cone biopsy [ 19 ]. For IA2 tumours, usually VRT with pelvic lymphadenectomy is chosen though some centres also use cone biopsy or ST combined with lymphadenectomy [ 20 ].…”
Section: Preoperative Workoutmentioning
confidence: 99%
“…In early cervical cancer, the status of regional lymph nodes is a critical factor in determining prognosis. Systematic pelvic lymph node dissection is routinely performed as part of standard surgical therapy, except stage IA1 [ 11 ]. Systematic pelvic lymphadenectomy is associated with short-and long-term morbidities, such as increased blood loss, neurovascular injury, lymphocyst formation and infection, and lowerlimb lymphedema [ 3 ].…”
Section: Introductionmentioning
confidence: 99%